Une définition territoriale de l’acceptabilité sociale : pièges et défis conceptuels - Yann Fournis; Marie-José Fortin (VertigO)
Embarrassing, the notion of "social acceptability" is gradually gaining credibility both in scientific and social terms. In Quebec, some dynamic researches allow, to some extent, to offer a definition avoiding partially its initial bias to explore some dynamics of the current crisis of the model of development based upon natural resources in the Province. In particular, it can highlight the delegitimization of a certain historical type of economic development (which is no longer immediately “acceptable”) and the fierce society debates that this crisis entails during the implementation of some major projects. In this sense, the notion allows to conveniently re-study the relationship between technology and territory, providing that we chose a dynamic (in terms of “acceptability” and not “acceptance”), political (and non-functionalist) and specifically territorial (and not generic or abstract) sense. On this basis, we propose an analytical grid of the processes at work in the collective assessment of a project within a territory, distinguishing three scales (macro-economic, meso-political and micro-social). Linking historical trends of development, struggles of legitimacy and socio-technical controversies and negotiations, this definition intends to take account seriously one of the forgotten factors of economic development: the territories, to examine if they can become actor in their own development.